Students’ Collaborative Skills in the Implementation of Collaborative Learning: A Qualitative Descriptive Study - Titin; Eko Sri Wahyuni; Nanda Emilia; Siti Komaria (Universitas Tidar, 2024)
The purpose of this study was to implement Collaborative Learning to determine the collaboration skills of students in the Biology Education Study Program, FKIP, Tanjungpura University. This study is a qualitative descriptive study. This study was conducted in 5 stages of learning, namely learning orientation, formation of study groups, task arrangement, facilitating learning collaboration, and giving grades and evaluating learning. The sample in this study consisted of 50 students who took the learning and teaching course. The instrument used in this study was a collaboration skills questionnaire consisting of 5 aspects that were assessed, namely contribution, time management, problem-solving, investigation techniques, and synthesis. The results of the data analysis obtained that the contribution aspect received a score of 87.5%; the time management aspect 85.5%; problem-solving aspect 89.4%; investigation technique aspect 93.5%; synthesis aspect 91%, with an average of all aspects of the 89.6% in the very strong category. So it can be concluded that the implementation of Collaborative Learning in learning and teaching courses can develop the collaboration skills of students in the biology education study program, FKIP, Tanjungpura University